Changes in mechanical properties of adipose tissue after bariatric surgery driven by extracellular matrix remodelling and neovascularization are associated with metabolic improvements. (15th March 2022) - Unamuno, Xabier; Gómez-Ambrosi, Javier; Becerril, Sara; Álvarez-Cienfuegos, Francisco Javier; Ramírez, Beatriz; Rodríguez, Amaia; Ezquerro, Silvia; Valentí, Víctor; Moncada, Rafael; Mentxaka, Amaia; Llorente, Marcos; Silva, Camilo; et al.
Abstract: Biomechanical properties of adipose tissue (AT) are closely involved in the development of obesity-associated comorbidities. Bariatric surgery (BS) constitutes the most effective option for a sustained weight loss in addition to improving obesity-associated metabolic diseases including type 2 diabetes (T2D). We aimed to determine the impact of weight loss achieved by BS and caloric restriction (CR) on the biomechanical properties of AT. BS but not CR changed the biomechanical properties of epididymal white AT (EWAT) from a diet-induced obesity rat model, which were associated with metabolic improvements. We found decreased gene expression levels of collagens and Lox together with increased elastin and Mmps mRNA levels in EWAT after BS, which were also associated with the biomechanical properties. Moreover, an increased blood vessel density was observed in EWAT after surgery, confirmed by an upregulation of Acta2 and Antxr1 gene expression levels, which was also correlated with the biomechanical properties. Visceral AT from patients with obesity showed increased stiffness after tensile tests compared to the EWAT from the animal model. This study uncovers new insights into EWAT adaptation after BS with decreased collagen crosslink and synthesis as well as an increased degradation together with enhanced blood vessel density providing, simultaneously, higher stiffness and more ductility. Statement of Significance: Biomechanical properties of the adipose tissue (AT) are closely involved in the development of obesity-associated comorbidities. In this study, we show for the first time that biomechanical properties of AT determined by E, UTS and strain at UTS are decreased in obesity, being increased after bariatric surgery by the promotion of ECM remodelling and neovascularization. Moreover, these changes in biomechanical properties are associated with improvements in metabolic homeostasis. Consistently, a better characterization of the plasticity and biomechanical properties of the AT after bariatric surgery opens up a new field for the development of innovative strategies for the reduction of fibrosis and inflammation in AT as well as to better understand obesity and its associated comorbidities. Graphical abstract: Image, graphical abstract